Meeting climate targets can only spur on economic growth with the right combination of measures - Timm Bönke; Geraldine Dany-Knedlik; Werner Röger (DIW Weekly Report, 2023)
Reducing carbon emissions is essential to meeting climate targets. What is unclear, however, is which measures are required to do so and what impact they would have on economic growth. In this Weekly Report, a macroeconomic model is used to observe four scenarios in comparison to a baseline scenario without emissions reduction. It is analyzed which effects different measures, such as technological progress developing at an increased speed and/or carbon pricing, would have on economic growth and emissions targets. Assuming that energy-saving technological progress develops as it has in the past, meeting the emissions targets will require a relatively high carbon price, which has a dampening effect on economic growth. If energy-saving technological progress were to develop at a faster pace, emissions targets could be met without carbon pricing and there would be slight growth. Therefore, consideration should be given to how much accompanying economic and climate policy measures can mitigate potential growth losses and distributional effects.
Keywords: Q43; E3; E6; 330; Potentialwachstum; Klimawandel; Energiewende; CO2 Preis